ACCELERATION ON THE GROWTH OF RUBBER PLANTING MATERIALS BY USING FOLIAR APPLICATION OF HUMIC ACID - Cahyo, Andi Nur; Ardika, Risal; Saputra, Jamin; Wijaya, Thomas (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2014)
The best rubber planting materials are needed to build the best rubber plantation. Humic acids could be used to improve the growth of rubber planting materials. Humic acid plays a role as a hormone-like substance. This research was aimed to determine the optimal concentration of foliar application of humic acid in order to enhance the growth of rubber tree planting materials. This research was arranged in a completely randomized block design with five treatments and four replicates. The treatments were the concentrations of humic acids, i. e. 0; 250; 500; 750; and 1,000 ppm. Observations were made on rubber tree diameter, plant height, shoot and root biomass, and nutrient content of leaves and the stem. The results showed that foliar application of 1,000 ppm of humic acids could enhance the growth of rubber tree planting materials. Foliar application of 500 â 1,000 ppm of humic acids could increase K content of the stem. The effects of foliar application of humic acids were more apparent in the root part than in the shoot part.Keywords : Hevea brasiliensis, humic acid, growth, hormone, nutrient uptake, and planting materials